2014
DOI: 10.1001/jamaneurol.2014.1472
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glatiramer Acetate Therapy on Functional Properties of B Cells From Patients With Relapsing-Remitting Multiple Sclerosis

Abstract: IMPORTANCEThis study describes what is, to our knowledge, the previously unknown effect of glatiramer acetate therapy on B cells in patients with relapsing-remitting multiple sclerosis (MS).OBJECTIVE To determine whether glatiramer acetate therapy normalizes dysregulated B-cell proliferation and cytokine production in patients with MS. DESIGN, SETTING, AND PARTICIPANTS Twenty-two patients with MS who were receiving glatiramer acetate therapy and 22 treatment-naive patients with MS were recruited at The Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 39 publications
3
73
2
Order By: Relevance
“…We have recently demonstrated that B cells from RRMS patients, but not healthy donors (HD), are hyper-responsive to CD40 stimulation as measured by proliferation (19, 20, 22, 30). Based on this data, we hypothesized that dysregulation of CD40 signaling contributes to the hyperactivity of B cells from RRMS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that B cells from RRMS patients, but not healthy donors (HD), are hyper-responsive to CD40 stimulation as measured by proliferation (19, 20, 22, 30). Based on this data, we hypothesized that dysregulation of CD40 signaling contributes to the hyperactivity of B cells from RRMS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, B cells from glatiramer acetate (Copaxone) treated MS patients no longer display hyper-responses to low-dose CD40 stimulation (20). To understand why B cells from MS patients exhibit a hyperactive response to CD40, we asked whether key signaling intermediates downstream of CD40 displayed enhanced activity.…”
Section: Introductionmentioning
confidence: 99%
“…Wilcoxon rank-sum test AQP4-IgG sero-positive and -negative NMOSD are similar in their immunopathogenesis and clinical course, or whether AQP4-IgG seronegative cases belong to a distinct subtype of NMOSD with features closer to MS [15,19]. In our patients with AQP4-IgG seropositive NMOSD, GA therapy was clearly not effective, indicating that modulation of autoimmune mechanisms by GA, as demonstrated in experimental autoimmune encephalomyelitis [13,14] and MS patients, [20] may be insufficient to suppress the immune process in NMOSD. Our findings are in agreement with a small case series of five AQP4-IgG seropositive NMOSD patients, who failed to respond to GA therapy [21].…”
Section: Discussionmentioning
confidence: 67%
“…The role of B cells in MS and EAE has generated increasing interest (12, 46, 51-55). Distinct B cell subtypes have recently been associated with EAE disease progression and regulation (6, 7, 16, 53, 56-59), and are at least partially dependent on the choice of antigen (protein or peptide) used to induce the disease (18). A role for B cells has also been suggested in different models of recombinant MOG (rMOG)-induced EAE (18, 60-62).…”
Section: Discussionmentioning
confidence: 99%
“…Bregs also have a role in the mechanism of action by Copaxone ® , a glatiramer acetate copolymer, approved for the treatment of relapsing-remitting MS (5, 12, 25, 52, 56). In a recent clinical trial, Ireland et al showed that treatment of relapsing-remitting MS patients with glatiramer acetate restored IL-10 production while reducing lymphotoxin-α production by peripheral B cells, thus contributing to the therapeutic effects of glatiramer acetate (53). This finding further supports our contention that IL-10-producing Bregs contribute to suppression of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%